Friction Spot Joining of AA6061 to Pre-holed Pure Copper Sheets with a Snap Rivet Head Die - Tahseen Yassin Yousef; Sabah Khammass Hussein; Hamed Ali Hussein (Journal of Techniques)
This work aims to join AA6061 to Copper sheets using friction spot joining technique without formation of intermetallic compounds (IMCs). Aluminium (Al) sheets were arranged with a lap joint configuration over a pre-holed copper sheet. A snap die was used under the copper specimen. A rotating tool was utilized to carry out the joining technique by friction at the common surface between the tool shoulder and Al surface. Three process parameters were selected to study its influence on the joint quality: rotating speed, pre-heating time, and plunging depth of the tool. Two materials were joined by extruding the Al metal through the copper hole, and forming a rivet head. The results indicated the two materials joined by mechanical interlock at an interface line of a micro-scale, without forming IMCs or presence of defects like cracks, voids or gaps. The extruded aluminium through the rivet head die prevented pull-outing the joint. The plunging depth of the tool exhibited the highest influence on the joint’s shear force which recorded a maximum value of 1800N.